Tegur Sapa Penjual dan Pembeli di Pasar Tradisional Surya Kusuma Semarang - Sri Puji Astuti (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
The market is where sellers and buyers meet. Meeting the sellers and buyers in traditional markets cause them to greet each other. For that purpose, they use the greeting word in interacting. What greetings are used in the traditional market of Surya Kusuma Semarang is discussed in this paper. Data collection was done by using observation method developed with basic technique of tapping and advanced technique in the form of notes technique and recording technique. Based on the results of research of greeting words used in traditional markets covers pronouns, relatives, limbs, title, profession, greeting intimate, and greeting where self. Speakers use greeting words by considering physical appearance, gender, and age. The greeting word is used by the seller to greet the buyer with the intention of captivating the buyer. Therefore, his merchandise is selling well